2012
DOI: 10.1007/s00122-012-1955-y
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide predictions from maize single-cross data

Abstract: Maize (Zea mays L.) breeders evaluate many single-cross hybrids each year in multiple environments. Our objective was to determine the usefulness of genomewide predictions, based on marker effects from maize single-cross data, for identifying the best untested single crosses and the best inbreds within a biparental cross. We considered 479 experimental maize single crosses between 59 Iowa Stiff Stalk Synthetic (BSSS) inbreds and 44 non-BSSS inbreds. The single crosses were evaluated in multilocation experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
145
6
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(169 citation statements)
references
References 27 publications
16
145
6
2
Order By: Relevance
“…Massman et al (2013) reported that RCGS had a superior response for stover yield, as well as stover and grain yield indices that were 14-50% higher than those of MARS. Recently, in tropical maize, by employing RCGS on eight bi-parental populations evaluated under drought stress environments, Beyene et al (2015) reported an average gain of 0.086 ton ha −1 per cycle, and hybrids derived from cycle 3 produced 7.3% (0.176 ton ha −1 ) higher grain yield than those from cycle 0 and conventional pedigree breeding methods.…”
Section: Rapid Cyclingmentioning
confidence: 99%
“…Massman et al (2013) reported that RCGS had a superior response for stover yield, as well as stover and grain yield indices that were 14-50% higher than those of MARS. Recently, in tropical maize, by employing RCGS on eight bi-parental populations evaluated under drought stress environments, Beyene et al (2015) reported an average gain of 0.086 ton ha −1 per cycle, and hybrids derived from cycle 3 produced 7.3% (0.176 ton ha −1 ) higher grain yield than those from cycle 0 and conventional pedigree breeding methods.…”
Section: Rapid Cyclingmentioning
confidence: 99%
“…It allows estimating the variance components by REML and the predicting the genetic values using the BLUP (Henderson, 1975;Resende, 2002;Massman et al, 2013). BLUP predictors and REML estimators allow inferences regarding the additive and non-additive genetic effects related to the GCA and SCA (Piepho et al, 2008;Möhring et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nakaya & Isobe (2012) argumentam que marcadores em LD significativo com os QTLs de interesse, em geral, não são mantidos em diferentes cruzamentos, o que dificulta o uso da GWS. Como exemplo, se efeitos de marcadores forem estimados a partir de híbridos simples de milho, os valores genético-genômicos estimados em populações heterogêneas não fornecem informações acuradas (Massman et al, 2013). Harris et al (2009), ao utilizar duas raças de bovinos como populações de referência, verificaram que o uso de uma raça como população de referência e de outra raça para validação resulta em baixa acurácia (-0,10 a 0,3).…”
Section: Resultsunclassified